Rp-hplc method development, validation for quantification of paracetamol and ibuprofen and its related impurities in solid dosage form - R SATYANARAYANA MURTHY; HANIMI REDDY BAPATU; MARAM RAVI KUMAR B; JOY SUNANDAN B (International Journal of Pharma and Bio Sciences, 2017)
A new simple, rapid, selective, precise and accurate simple gradient RP-HPLC method has been developed for the estimation impurity profile of Paracetamol and Ibuprofen combination in tablet formulation. The high resolution separation was achieved by using Agilent Poroshell 120 EC-C18, 2.7 µm 100x4.6 mm coupled with a guard column. Separation mobile phase A and B were prepared with high pure solvents and Milli-Q grade water. Buffer solution was prepared with 1000 mL of Milli-Q water and further adjusted the pH 2.5 with diluted OPA solution. Mobile Phase-A: Prepared a mixed solution with buffer solution 950 mL and 50mL with Methanol. Mobile Phase-B: Prepared a mixed solution with 200 mL of buffer solution, 200 mL of Acetonitrile and 600 mL of Methanol. Both mobile phase A and B were degassed with 0.45 µ filter. The flow rate was 1.0ml/min; UV-220nm; Ambient column temperature; 55 min runtime; 10 µL injection volume. Gradient program includes time points 0, 5, 15, 30, 40, 45, 46 and 55 min; mobile phase-A% volume is 95, 95, 50, 50, 30, 30, 95 and 95%; M.P.-B% volume is 5, 5, 50, 50, 70, 70, 5 and 5%. The method was validated as per ICH guidelines. The proposed method was found to be accurate, repeatability and consistent. It was successfully applied for the analysis of the drug in marketed formulation and could be effectively used for the routine analysis of formulation containing the drug without any alteration in the HPLC conditions